Limits of competence of a forensic commodity expert in determining the characteristics of goods in cases of customs rules violation - S. О. Diachuk (Bulletin of Kharkiv National University of Internal Affairs)
Today, all goods, regardless of the country of origin, are subject to classification, that is, codes are determined for goods in accordance with the classification groupings specified in the UCC of the Economic and Monetary Union. Expertise on determining the conformity of the characteristics of goods according to the UCC FEA, regardless of the purpose of establishing the code, is only a means of establishing the circumstances of implementation, that is, the characteristics on which the definition of the goods code is based, but by its task it cannot support the adoption of a decision on the determination interpretation of the product code according to the UCC FEA. Understanding the correctness of drawing up an expert's opinion allows to avoid difficulties when conducting a forensic commodity examination.